2013
DOI: 10.1007/s11999-013-3133-1
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Local Tissue Reaction Associated With a Modular Hip Hemiarthroplasty

Abstract: Background The local and systemic effects of wear

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 19 publications
1
37
0
2
Order By: Relevance
“…With pseudotumour formation and development of an inflammatory response, significant soft tissue damage can ensue. ALTR is most commonly described in MoM THR but also occurs in MoP THR 4,5,10,11 and even modular hemiarthroplasty 19 . The presented series describes significant ALTR and secondary pseudotumour formation in a cohort of MoP THR patients.…”
Section: Discussionmentioning
confidence: 99%
“…With pseudotumour formation and development of an inflammatory response, significant soft tissue damage can ensue. ALTR is most commonly described in MoM THR but also occurs in MoP THR 4,5,10,11 and even modular hemiarthroplasty 19 . The presented series describes significant ALTR and secondary pseudotumour formation in a cohort of MoP THR patients.…”
Section: Discussionmentioning
confidence: 99%
“…First, by confining our review to studies that included quantitative or semiquantitative grading of the histologic findings, we excluded many publications that have used only qualitative descriptions of periarticular findings [5,12,29,35,42,44,46] or that have focused on particle quantitation [13,30,45], cytokine detection [9,21], or lymphocyte subsets [29]. Among the studies that have graded morphologic features of periprosthetic tissues, many have not included conventional metal-on-PE or ceramic-on-polyethylene cases as controls, and differences in grading criteria among studies preclude pooling the data into larger groups.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the final articles were removed because they addressed corrosion secondary to stem loosening and a knee modular revision component. This left nine articles focused on corrosion in femoral hip components [9,10,23,29,32,37,42,46,47].…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…There were nine studies identified addressing the surgical treatment of implant failures secondary to taper corrosion (Table 5) [9,10,23,29,32,37,42,46,47]. Eight articles were case report studies and one was Level IV.…”
Section: Treatment Of Corrosionmentioning
confidence: 99%
See 1 more Smart Citation